Repellency and Reduction of Offspring Emergence Potential of Some Botanical Extracts against Sitophilus zeamais (Coleoptera: Curculionidae) in Stored Maize - Diaine Cortese; Matheus Moreno Mareco Da Silva; Gisele Silva de Oliveira; Rosilda Mara Mussury; Marcos Gino Fernandes (Insects, 2022)
Botanical repellents are, usually, considered safe to control Sitophilus zeamais, the main pest of stored maize, as they do not leave toxic residues in food, in addition to having lower costs than chemical insecticides. The aim of this study was to evaluate the repellency potential and the reduction of emerged offspring of botanical extracts, of Schinus terebinthifolius, Ludwigia sericea, L. tomentosa, L. nervosa, L. longifolia, and use them as botanical insecticides for S. zeamais. For the repellency test, arenas were set up, containing 50 g of maize kernels exposed to aqueous extract, besides a control treatment. At the center of each arena, 100 insects were released. After 48 h, the proportion of insects in the treated grains was determined. To test the effects of the extracts on insect mating and egg-laying, free-choice and no-choice tests were performed. Insects in both tests remained for ten days for mating and egg-laying. After this period, insects were removed to evaluate the offspring emergence. Sixty days after grain infestation, the number of emerged insects was counted. All selected botanical extracts demonstrated repellent action against S. zeamais, even after 48 h of application. The L. nervosa aqueous extract significantly reduced the emergence of S. zeamais.